Needs Analysis for Designing English for Hotel Management Students at SMKN 1 Sumbawa Besar - Wanda Juita Sari; I Made Sujana; Agus Saputra; Muhammad Amin (Journal of English Education Forum (JEEF), 2026)
This study analyzes the English language needs of Hotel Management students at SMKN 1 Sumbawa Besar to design more relevant English for Specific Purposes (ESP) materials. Using questionnaires distributed to 29 students, interviews with two teachers, and documentation, the research found that students face challenges in speaking, vocabulary, pronunciation, and listening, while English is highly needed for tasks such as greetings, reservations, check-in/out, telephone communication, and handling complaints. Current learning still emphasizes General English, creating a gap with industry demands. The study recommends that an ESP-based syllabus focus on Front Office English through role-plays, simulations, and authentic materials to enhance students’ communicative competence and workplace readiness.